PENINGKATAN KETERAMPILAN KOMUNIKASI DAN HASIL BELAJAR PESERTA DIDIK BERBANTU CANVA DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Wahyuningtyas, Amelia Catur; Puspitasari, Yulia Dewi (Papua Journal of Physics Education, 2024)
This research aims to describe the learning process of students and teachers in the classroom, describe the improvement in students communication skills (communication skills) and describe the process of improving learning outcomes by students and teachers with the help of Canva in Natural Sciences and Social Biology subjects at SMK Negeri 2 Bagor. The type of research used is classroom action research. This research has action steps starting with planning, taking action, observing, and finally reflecting. This research took place over three cycles with 36 class X ATPH 1 students as the subject. The results obtained in this study showed that there was an increase in communication skills and student learning outcomes that the scientific learning process was running according to the sequence of scientific steps in cycle I, reaching 76% in the sufficient category, in cycle II it increased to 84% in the good category, and in cycle III it increased to 94% in the very good category. Based on the overall research, it can be concluded that learning Natural Sciences and Social Biology with the help of Canva media can improve the communication skills and learning outcomes of class X ATPH 1 students at SMKN 2 Bagor Nganjuk